Pre-conception folic acid intake and attention deficit and hyperactivity disorder in children - Uzun, Mehmet Erdem; Kaymaz, Nazan; Aylanc, Hakan; Gökten, Emel Sarı; Şirin, Hande; Battal, Fatih (The European Research Journal, 2023)
Objectives: Attention Deficit Hyperactivity Disorder (ADHD) is a common disorder in children. It is thought to occur due to the interaction of many genetic and environmental factors during early  development. Many studies have been conducted to investigate the etiology of ADHD. Some have investigated neurobiology, and others have investigated malnutrition and trace element deficiency. To investigate the effect of folic acid intake during the pre-conception period in terms of ADHD development.Methods: Five hundred and ninety-eight participants, 246 children with ADHD, and 352 healthy controls were enrolled. A questionnaire was completed, including socio-demographic information and the use of folic acid and other supplements such as a multivitamin, iron, and omega 3 during pregnancy. Data were examined to determine associations with ADHD. Mann-Whitney U tests for continuous variables, Pearson’s chi-square, and Fisher’s exact tests for categorical variables were used to compare groups.Results: The use of folic acid during pre-pregnancy among mothers who had a child with ADHD was 13% and this was 31% in the control group (p < 0.001). There was no statistically significant difference between the groups’ use of folic acid in pregnancy (p = 0.617). Other situations related to ADHD were advanced maternal age (p < 0.001 for both groups), abnormal double screening test results in pregnancy (27% vs. 5%, p < 0.001) and omega 3 use in pregnancy (p < 0.001).Conclusions: The use of folic acid before and during pregnancy is important for neurological development. However, there is little data on use before pregnancy in the literature. This study shows that folic acid taken before pregnancy may prevent ADHD in childhood. The present study recommends folic acid usage in planned pregnancy to prevent ADHD in the child.